The polar exploration diary of Mark Wood: a thematic content analysis. Issue 1 (2nd January 2017) - Suedfeld, Peter; Shiozaki, Lisa; Archdekin, Ben; Sandhu, Harbinder; Wood, Mark
Abstract: Mark Wood, a British explorer who skied alone and unsupported to the Geographic South Pole in a 2011/12 expedition, made his exploration diary available for thematic content analysis (TCA). TCA comprises a number of scoring systems measuring various psychological processes, including aspects of cognition, motivation and personality. The diary entries were analysed for coping strategies, motive imagery, personal values and post-experience growth. The results showed a conscientious, practical and achievement-oriented approach, actions to raise the level of stimulation and concern for the environment (the declared purpose of the trek). Although this study of one individual precludes generalisations, some of the results may point to personality differences specific to solo explorers/adventurers as opposed to group participants.